Two illegitimate superfluous names in Premna (Lamiaceae, Premnoideae) - Li, Bo (Phytotaxa, 2018)
When compiling Flora Yunnanica, Wu (1977) described six new species in the genus Premna Linnaeus (1771: 587), including P. laevigata Wu (1977: 440), P. oligantha Wu (1977: 434), P. punicea Wu (1977: 433), P. rubroglandulosa Wu (1977: 431), P. straminicaulis Wu (1977: 426), and P. velutina Wu (1977: 428). All these species were recognized in the account of Premna of Flora Reipublicae Popularis Sinicae (P’ei & Chen, 1982), and in its English updated edition, Flora of China (Chen & Gilbert, 1994). Unfortunately, P. laevigata C.Y.Wu and P. velutina C.Y.Wu are two illegitimate names according to Art. 53.1 of the ICN (McNeill et al. 2012) because they are later homonyms of P. laevigata Miquel (1858: 895) and P. velutina Gürke (1895: 338), respectively. The illegitimacy of the two names was later realized by Boufford & Bartholomew (2012) and Li et al. (2013), proposing the names P. wuii (noting this “wuii” as “wui”) Boufford & Bartholomew (2012: 1) to replace the name P. velutina C.Y.Wu, and P. menglaensis Li (2013: 58) to replace the name P. laevigata C.Y.Wu, respectively.